y*y=26-1

Simple and best practice solution for y*y=26-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y*y=26-1 equation:



y*y=26-1
We move all terms to the left:
y*y-(26-1)=0
We add all the numbers together, and all the variables
y*y-25=0
Wy multiply elements
y^2-25=0
a = 1; b = 0; c = -25;
Δ = b2-4ac
Δ = 02-4·1·(-25)
Δ = 100
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$y_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$y_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{100}=10$
$y_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(0)-10}{2*1}=\frac{-10}{2} =-5 $
$y_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(0)+10}{2*1}=\frac{10}{2} =5 $

See similar equations:

| j+11=-24 | | 2m+4m+4=10 | | x/12=10/12 | | 0.3x+10=2x-5 | | 0.33x+10=2x-5 | | x-5x-60=-12 | | 19=x^2-6 | | 15+9x+72=180 | | 3/7x+4=10 | | 51-10x=19+6x | | 0.333x+10=2x-5 | | 2x-11x+3=21 | | 12=0.60•x | | 3c+c-3c-c+c=14 | | 5(3x+7)−1=3(5x)+4 | | -99=k+-53 | | 22.4=x7 | | (q-6)×3=18 | | 14c+2c-9-2c=5 | | 3j+10j+10=10j-8 | | 5e-10-3=8e+4-4 | | 6x+80=x+30 | | 7m-13=43m= | | 8+5d=7d | | 80=4t | | q+10=22 | | 4v+5v-6v=12 | | -24n+5=2n+24 | | 10x-52.5=7x | | 2n+13−8n=5 | | 2×3x=30 | | 15p-14p=12 |

Equations solver categories